(3GdYbhHI GdeGdjI ZjQ GdebOQIs - (3eMeO YHO QHg eMeO(B, (3GdSHMjs ((3GdGScfOQjI(B:s (3OGQ GdacQ GdLGeYj,s, 2007)
(3jVe JYQja GdYbhHI hCfhGYgG hGdaQb Hjf GdLeGjI hGdLQjeI hMceI JTQjY GdYbhHI, aj JYQja GdJYRjR hGdaQb Hjfg hHjf GdMO hUaGJg hWQb GKHGJg hUhQ GdeYGUj GdJj JhLH GdJYRjR, aj BQGA GdabgGA aj eSCdI GdYbhHI GdeGdjI GdZjQ ebOQI, ebGQfI Hjf QCj GdGeGe GdZRGdj ef MLjI GdeUdMIs
(3HjHdjhZQGajG(B: (3U(B.139s
Keywords: (3GdYbhHGJs; (3bGfhf GdYbhHGJ GdeGdjI s